The Effect of ChatGPT as an AI-Assisted Reading Tool on the Critical Reading Skills of English Education Students at FBMB, UNDIKMA - Firman, Edi; Sudirman, Sudirman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study investigates the effect of ChatGPT, an AI-assisted reading tool, on the critical reading skills of English Education students at the Universitas Pendidikan Mandalika (UNDIKMA). The research was motivated by the need to enhance students’ critical literacy, which remains a persistent challenge in English as a Foreign Language (EFL) context. Employing a quasi-experimental design, the study involved two groups of third-semester students enrolled in a Critical Reading course: an experimental group that used ChatGPT to support reading activities, and a control group that received traditional instruction without AI assistance. Over a six-week intervention, the experimental group interacted with ChatGPT to clarify vocabulary, summarize texts, analyze arguments, and generate comprehension questions, while the control group followed conventional reading procedures. Data were collected through pretests, posttests, questionnaires, and interviews. Quantitative analysis using paired-sample and independent-sample t-tests revealed that the experimental group achieved a significantly higher mean gain (M = 18.06, p < .001) compared to the control group (M = 8.20, p < .001), with a large effect size (Cohen’s d = 1.37). Qualitative findings indicated that students perceived ChatGPT as engaging, helpful for understanding complex texts, and effective in developing critical awareness. However, some expressed concerns about potential overreliance on AI-generated responses. The study concludes that ChatGPT can serve as an effective pedagogical tool to enhance EFL students’ critical reading skills when integrated thoughtfully and ethically. It recommends that educators provide structured guidance in using AI tools to foster analytical thinking, autonomy, and responsible digital literacy in higher education reading courses.